Lack of association between cortical amyloid deposition and glucose metabolism in early stage Alzheimer ́s disease patients - Ehrlich, Daniela; Dunzinger, Andreas; Malsiner-Walli, Gertraud; Grün, Bettina; Topakian, Raffi; Hodolic, Marina; Kainz, Elmar; Pichler, Robert (Radiology and oncology, 2021)
BACKGROUND: Beta amyloid (Aβ) causes synaptic dysfunction leading to neuronal death. It is still controversial if the magnitude of Aβ deposition correlates with the degree of cognitive impairment. Diagnostic imaging may lead to a better understanding the role of Aβ in development of cognitive deficits. The aim of the present study was to investigate if Aβ deposition in the corresponding brain region of early stage Alzheimer ́s disease (AD) patients, directly correlates to neuronal dysfunction and cognitive impairment indicated by reduced glucose metabolism. PATIENTS AND METHODS: In 30 patients with a clinical phenotype of AD and amyloid positive brain imaging, 2-[18F] fluoro-2-deoxy-d-glucose (FDG) PET/CT was performed. We extracted the average [18F] flutemetamol (Vizamyl) uptake for each of the 16 regions of interest in both hemispheres and computed the standardized uptake value ratio (SUVR) by dividing the Vimazyl intensities by the mean signal of positive and negative control regions. Data were analysed using the R environment for statistical computing and graphics. RESULTS: Any negative correlation between Aβ deposition and glucose metabolism in 32 dementia related and corresponding brain regions in AD patients was not found. None of the correlation coefficient values were statistically significant different from zero based on two-sided p- value. CONCLUSIONS: Regional Aβ deposition did not correlate negatively with local glucose metabolism in early stage AD patients. Our findings support the role of Aβ as a valid biomarker, but does not permit to conclude that Aβ is a direct cause for an aberrant brain glucose metabolism and neuronal dysfunction.
Keywords: Alzheimerova nemoc; fluorodeoxyglukosa F18; lidé; Fluorodeoxyglucose F18; amyloidní beta-protein; PET/CT; Amyloid beta-Peptides; glukosa; Positron Emission Tomography Computed Tomography; Alzheimer Disease; Glucose; Humans